Effect of thermal annealing on physical properties of vacuum evaporated In2S3 buffer layer for eco-friendly photovoltaic applications. (December 2015) - Nehra, S.P.; Chander, S.; Sharma, Anshu; Dhaka, M.S.
Abstract: The present communication reports the effect of thermal annealing on the physical properties of In2 S3 thin films for eco-friendly buffer layer photovoltaic applications. The thin films of thickness 150 nm were deposited on glass and indium tin oxide (ITO) coated glass substrates employing thermal vacuum evaporation technique followed by post-deposition thermal annealing in air atmosphere within a low temperature range 150–450 °C. These as-deposited and annealed films were subjected to the X-ray diffraction (XRD), UV–vis spectrophotometer, current–voltage tests and scanning electron microscopy (SEM) for structural, optical, electrical and surface morphological analysis respectively. The compositional analysis of as-deposited film is also carried out using energy dispersive spectroscopy (EDS). The XRD patterns reveal that the as-deposited and annealed films (≤300 °C) have amorphous nature while films annealed at 450 °C show tetragonal phase of β-In2 S3 with preferred orientation (109) and polycrystalline in nature. The crystallographic parameters like lattice constant, inter-planner spacing, grain size, internal strain, dislocation density and number of crystallites per unit area are calculated for thermally annealed (450 °C) thin films. The optical band gap was found in the range 2.84–3.04 eV and observed to increase with annealing temperature. The current–voltage characteristics show that the as-deposited and annealed films exhibit linear ohmic behavior. The SEM studies show that the as-deposited and annealed films are uniform, homogeneous and free from crystal defects and voids. The grains in the thin films are similar in size and densely packed and observed to increase with thermal annealing. The experimental results reveal that the thermal annealing play significant role in the structural, optical, electrical and morphological properties of deposited In2 S3 thin films and may be used as cadmium-free eco-friendly buffer layer for thin films solar cells applications.